The Influence Of Service Quality On Customer Satisfaction At Bank Syariah Indonesia KCP Probolinggo - Khoiril Anam; Romzatul Widad (International Journal of Science and Environment (IJSE), 2025)
This study aims to analyze the effect of service quality on customer satisfaction both partially and simultaneously at Bank Syariah Indonesia Probolinggo Branch. This type of research is descriptive quantitative. The population in this study were all consumers of Bank Syariah Indonesia Probolinggo Branch. The sample size was 100 respondents. Validity test and reliability test are used to test measuring instruments. The results showed that responsiveness with a coefficient of 0.003, assurance with a coefficient of 0.016, tangible with a coefficient of 0.037, reliability with a coefficient of 0.040 had an effect on customer satisfaction. The coefficient of determination analysis shows that 59.2% of customer satisfaction is influenced by service quality. While the remaining 40.8% is influenced by other variables not included in the study Thus, improving overall service quality can be an effective strategy in increasing customer satisfaction at BSI Probolinggo Branch.